Blood free fatty acids were not increased in high-fat diet induced obese insulin-resistant animals. Issue 2 (March 2016) - Jiang, Junfeng; Wu, Yongjie; Wang, Xiaoxia; Lu, Li; Wang, Li; Zhang, Baolai; Cui, Mingxia
Summary: Objective: The close connection between high blood FFA and insulin resistance (IR) in obese individuals is well-known. The purpose of this study was to identify whether the blood FFA increased in obese-IR animals. Methods: Obese-IR animal models were established using high-fat diet (HFD) or HFD and streptozocin, and treated with drugs. Results: The serum FFA of obese-IR animals was not increased, even significantly lower than that of normal animals, and were not significantly decreased when insulin sensitivity and obesity-related indices were ameliorated after treatment. Conclusion: The results suggest that blood FFA are unlikely the link between obesity and insulin resistance.